Crédito e taxa de juros: análise sobre os efeitos no setor habitacional brasileiro no período de 2010-2019 - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The real estate market is one of the segments of strong relevance to a country's economy, due to its production chain involving different segments in the construction process, promoting direct and indirect jobs and moving high financial investments in its transactions. This study aims to analyze how the countercyclical measures adopted from 2010 influenced the development of real estate activity in Brazil, in order to interpret the recessionary economic cycle from 2010 to 2019. For this, the research is based on the Austrian theory of economic cycles, which adheres to the logical deductive method as a basis for analysis. The method used by the Austrians shows that there is no static equilibrium, but a market process that evolves over time, involving changes in agents' knowledge.
Keywords: Crédito; Juros; Ciclos econômicos; Mercado imobiliário; Credit. fees; Economic cycles; Real estate market; CNPQ::CIENCIAS SOCIAIS APLICADAS